Immunodiagnostic for caprine artrithis encephalitis in flocks of semi-arid region in the State of Bahia Brazil - De Lima, Carla Caroline Valença; Costa, Joselito Nunes; De Souza, Thiago Sampaio; Martinez, Priscila Martinez; Neto, Antônio Oliveira Costa; Azevedo, Dalva Alana Aragão; Pinheiro, Raymundo Rizaldo; De Brito, Roberta Lomonte Lemos [UNESP] (My University, 2013)
This work had the purpose of standardizing the technique of indirect immunosorbent assay (i-Elisa) for the diagnosis of caprine arthritis- encephalitis (CAE) in flocks of Microregion of Juazeiro, and to compare the results obtained with other techniques. To attain our goal, we evaluated 693 blood serum samples of goats from 46 farms in this Microregion (Campo Alegre de Lourdes, Casa Nova, Curaçá, Juazeiro, Pilão Arcado, Remanso, Sento Sé and Sobradinho). About the seroprevalence obtained in i-Elisa, 1.59% (11/693) of the animals showed they possess the anticorps against the CAE's virus and 15.22% (7/46) of the properties had seropositive animal. Results of commercial AGID demonstrated that only 0.29% (2/693) of the samples were positive. Standard Elisa showed 100% sensitivity and 98.7% specificity, with kappa of 0.30 compared to the commercial AGID. Of the 693 samples, 65 were used in techniques of Immunoblotting (IB) and different AGID kits. There was no difference in the results obtained in the AGID kits, and IB demonstrated higher sensitivity than i-Elisa. Therefore, it is recommended to use different techniques such as AGID and Elisa in order to improve the diagnosis of CAE control programs.
Imunodiagnóstico para a artrite-encefalite caprina em rebanhos do Semiárido Baiano Brasil
Keywords: CAEV; Immunoassay; Serology; SRLV